Principles for a responsible integration of mindfulness in individual therapy - Michalak, Johannes; Mander, Johannes (Mindfulness, 2019)
Objectives: Mindfulness-based interventions (MBIs) like mindfulness-based stress reduction (MBSR) and mindfulness-based cognitive therapy (MBCT) teach mindfulness in a group-based format. Empirical research has shown that many therapists working in individual therapy integrate mindfulness practices (e.g., body scan, sitting meditation) into their treatments. However, research on this topic is in its infancy. The purpose of this paper is to present recommendations for a responsible use of mindfulness in individual therapy. Methods: Informed by a literature review, an expert group developed guidelines for a responsible use of mindfulness in individual therapy. Results: Recommendations for the following issues were developed: (a) different types of integration; (b) diagnoses/clinical problems for which integration of mindfulness in individual therapy could be useful; (c) qualification of therapists; (d) case formulation; (e) the inquiry process; (f) types and optimal duration of mindfulness practices in individual therapy; (g) managing difficult experiences; (h) integration of mindfulness into individual therapy training programs. Finally, we formulate important topics for research on the integration of mindfulness into individual therapy. Conclusions: By formulating recommendations for the most important issues of the integration of mindfulness into individual therapy, we want to stimulate the discussion on a responsible use of mindfulness in this setting. Since research on this topic is scarce, our recommendations can only be tentative.
Gesehen am 09.09.2019